Analysis and Strategy of Strengthening Green Economy Through the Value Chain ??Concept to Support Downstreaming of Coffee Farming in East Java - Ivo Rajava Fiba; Raissa Aulia Salsabila (East Java Economic Journal, 2025)
This study aims to analyze the coffee value chain and formulate strategies to strengthen downstream coffee farming in East Java Province within a green economy framework. Primary data were collected through surveys and interviews conducted in 2024 with three key actors: farmers, historians, and government officials. The analysis was conducted using the Hayami method to measure product added value, Rapfish to assess value chain variability, and AHP to determine priority strengthening strategies. The results indicate that the greatest added value is obtained when farmers process coffee from cherries to ground coffee. A unique analysis indicates that ecological and market dimensions still require further development. The resulting strategic priorities are training and certification of Good Agricultural Practices (GAP), facilitating market access through e-commerce and direct trade, and local government policies that encourage the use of local coffee. These findings emphasize the importance of downstream coffee processing as a means to enhance farmer welfare while promoting the transition to a green economy in East Java.